2019
DOI: 10.1097/bot.0000000000001409
|View full text |Cite
|
Sign up to set email alerts
|

Short Versus Long InterTAN Fixation for Geriatric Intertrochanteric Hip Fractures: A Multicentre Head-to-Head Comparison

Abstract: Objective: To determine if geriatric intertrochanteric hip fracture patients achieve equivalent postoperative functional status after management with either a short (180-200 mm) or a long (260-460 mm) InterTAN intramedullary device. Design: Retrospective review of a prospective randomized control trial. Setting: Four Level I Trauma Centers. Patients/Participants: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Five studies included information on the number of patients requiring blood transfusion, however only Boone et al . reported that there was a statistically significant difference in transfusion rates 18 , 25 27 , 31 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Five studies included information on the number of patients requiring blood transfusion, however only Boone et al . reported that there was a statistically significant difference in transfusion rates 18 , 25 27 , 31 .…”
Section: Resultsmentioning
confidence: 97%
“…and Shannon et al . , had a randomised controlled trail (RCT) design 27 , 28 , 33 . The remaining thirteen studies were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Sellan et al observed a better HHS for the short nail group, but did not find any significance from the clinical point of view. One hypothesis is that usually, cases with such fractures are geriatric patients with low motor functions required to return to the baseline (26).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction was the key factor to determine the operative effect of intertrochanteric fracture of femur [9]. Many complications, such as hip varus, loosening of internal xation, and refracture, were associated with poor reduction [10]. Poor reduction was more common in irreducible fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged bedridden could lead to pressure sores, pneumonia, deep vein thrombosis and other complications, and can lead to death. So the intertrochanteric fracture was called the "last fracture of life" [1]. Therefore, surgical treatment was the preferred choice for intertrochanteric fractures.…”
Section: Introductionmentioning
confidence: 99%